Miscarriage Rates Due to Endometriosis: A Retrospective Cohort Study - Calis, Pinar; Isik, Gizem; Duygulu, Dilara; Bozkurt, Nuray; Karcaaltincaba, Deniz (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: To find the differences of miscarriage rates between pregnant patients with and without endometriosis. STUDY DESIGN: The retrospective cohort study was conducted in the Department of Obstetrics and Gynecology, School of Medicine, Gazi University between January-2015 and December-2018. Patients were divided into two groups; endometriosis and non-endometriosis according to their pathology report and ultrasound examination. In both groups, miscarriage rates and in vitro fertilization pregnancy ratios were analyzed. Miscarriage rates in in vitro fertilization pregnancies and in endometriosis group who had and didn’t have surgery also analyzed. RESULTS: Sixty-two patients in the study group and 65 patients in the control group were included. There was no significant difference in miscarriage rates between endometriosis and non-endometriosis group (20/62 (32%) and 13/65 (20%), respectively, p=0.124). There was a statistically significant difference in miscarriage rates between in vitro fertilization and non-in vitro fertilization group (p=0.004). Apart from that, in in vitro fertilization group, the miscarriage rate was higher in the endometrioma subgroup than non-endometrioma (p=0.008). CONCLUSION: There was an only significant difference in miscarriage rate in the in vitro fertilization group between endometrioma and non-endometrioma patients. In the future, there should be more studies to define the actual pathophysiology for miscarriage with endometriosis.